2009
DOI: 10.1177/230949900901700205
|View full text |Cite
|
Sign up to set email alerts
|

Six-Year Experience with the Delta III Reverse Shoulder Prosthesis

Abstract: The Delta III prosthesis restores shoulder function but has biomechanical limits. Its use should be limited to elderly patients with severe impairment of the glenohumeral joint. Scapular notching is a main concern for the long-term survival of the implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 24 publications
(36 reference statements)
5
37
0
1
Order By: Relevance
“…All studies that reported this outcome measure showed a remarkably consistent improvement at a mean of 41.62 (range 39 to 46) points. This is comparable with studies looking at RSA in cuff tears (mean improvement of 43) [19,41,42] or cuff arthropathy (mean improvement of 41.33) [43][44][45] and suggests that outcome from RSA in RA is predictable.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…All studies that reported this outcome measure showed a remarkably consistent improvement at a mean of 41.62 (range 39 to 46) points. This is comparable with studies looking at RSA in cuff tears (mean improvement of 43) [19,41,42] or cuff arthropathy (mean improvement of 41.33) [43][44][45] and suggests that outcome from RSA in RA is predictable.…”
Section: Discussionsupporting
confidence: 70%
“…Erosion of the glenoid makes implanting a component more challenging, predisposing to less satisfactory fixation, instability and early implant failure. Previous authors advocated hemi-arthroplasty as the treatment of choice in patients with large glenoid defects, bypassing issues of replacing the eroded socket [19][20][21]. However functional results were poor and deteriorated with time after the procedure, predominantly due to progressive glenoid wear [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The major indication for using RTSA is arthritis associated with massive rotator cuff tears which accounts for approximately 90 % of the cases in different series [2,5,6,8,9,22]. The patient's age is important for the indication, as the implant longevity is not well understood; therefore, most authors do not advocate use of this type of implant for patients under 65 years of age [1,5,9,[23][24][25][26]. The use of reverse arthroplasty changes the Fig.…”
Section: Indicationsmentioning
confidence: 99%
“…25 Now, indications are expanding, with many patients undergoing RSA for various pathologies such as failed total shoulder arthroplasty or hemiarthroplasty, complex proximal humeral fractures and fracture malunion or nonunion, rheumatoid arthritis with rotator cuff lesions, and failed or irreparable massive rotator cuff tears. [2][3][4][6][7][8][9]12,13,[15][16][17][18][19][20][21][22]24,28,29,31 Reported complications after RSA are worrisome and common. They can range from mechanical failures of the prosthesis, infection, and instability to intraoperative fractures.…”
mentioning
confidence: 99%
“…It has been described in all followup studies of RSA, with rates as high as 9%, accounting for almost half of the complications in some series. 1,[4][5][6][7][8]10,11,15,16,18,[26][27][28][29]30,31 Methods to reduce the incidence of dislocation after RSA are currently being examined. In this study, we investigated the effect of subscapularis repair on any report or findings of complications, including subset analyses of dislocation, infection, disassociation, and fracture after RSA with the Reverse Shoulder Prosthesis (RSP, DonJoy Surgical, Austin, TX, USA).…”
mentioning
confidence: 99%